Effects of pH and Aluminum on Growth of Rhizobia and the Relationship between Fatty Acid Composition of Rhizobia and its Tolerance to Low pH - Muhamad Idris, Shaharah (1996)
The effect of two different initial culture pHs on growth of six stranis of rhizob a (TAL 102, was first studeid by using shake flask expermient. Only B radyrhizobium TAL 102 grew better at pH 4.5 compared to 6. and this strain was chosen as an acid -to lerantrhizobia. This result is in agreement with the result of the experiment using the fermenter in which the culture pH was controlled at a constant value of 4.5 and 6.5 throughout the cultivation. However, parameters such as maximum cell concentration attained (Xm) differed significantly.